Assessment of Ply Stacking Sequence Effect on Damage Behavior of CFRP Composite Laminate Under Low-Velocity Impacts - Murlidhar Patel; Lokesh Sonkar; Shivdayal Patel (Advances in Materials Science and Engineering)
To enhance performance under low-velocity impact (LVI), the ply stacking sequence of a composite laminate must be carefully selected. To guarantee that the laminate can sustain the projected impact energy, the impact load should be carefully evaluated during the design phase. To obtain an optimized stacking layup orientation, the damage behaviors of excellent specific strength carbon fiber–reinforced polymer (CFRP) composite laminates with stacking sequences of [0°]8 (unidirectional), [0°/90°]2s (cross-ply), [0°/+45°/−45°/90°]s (quasi-isotropic), and [0°/−30°/−60°/−90°/90°/60°/30°/0°] (antisymmetric) were numerically investigated under LVI. Throughout the investigation, 1 to 2 kg of impactors were employed at a velocity of 3.835 m/s. The damage initiations in composite laminates were assessed using both Hashin’s criteria and the Puck–Schurmann criterion. For predicting delamination between composite plies, the quadratic nominal stress delamination failure criteria were applied. For the study of composite damage behavior under LVI, the time-dependent changes in impact-resisting force, force versus displacement, and time-dependent variations in the internal energy of the composite laminates were taken into consideration. The predicted results show that in comparison with the other three configurations, the composite laminate with a ply arrangement of [0°/+45°/−45°/90°]s (quasi-isotropic) exhibited a stronger impact-resisting force, smaller peak displacement, fewer deformations, and a smaller amount of damage with superior rebound energy.